CONSTRAINTS ON THE AGE OF FORMATION OF SEISMICALLY REFLECTIVE MIDDLE AND LOWER CRUST BENEATH THE BERING SHELF: SHRIMP ZIRCON DATING OF XENOLITHS FROM SAINT LAWRENCE ISLAND - Miller E.L.; Ireland T.R.; Klemperer S.L.; Wirth K.R.; Akinin V.V.; Brocher T.M. (My University, 2002)
Seismic reflection and/or refraction studies reveal reflective middle and lower crust and a sharp Moho (~32 km depth) beneath a broad region of the Bering Shelf between Alaska and northeast Russia. Basalt flows on Saint Lawrence Island of the late Cenozoic Bering Sea basalt province contain upper mantle and crustal xenoliths that include mafic cumulate rocks and lesser pyroxene-bearing gneisses that equilibrated at ~4-6 kbar. The gneissic xenoliths are interpreted as intrusive rocks that acquired deformation and/or recrystallization fabrics during granulite facies metamorphism. Three gneissic xenoliths from two sites yielded zircons that were dated by the UPb method with the SHRIMP II (sensitive high resolution ion microprobe). Zoned prismatic zircons of magmatic origin yield ages mostly ca. 85-90 Ma. Rounded, nonzoned zircons from other samples are likely metamorphic in origin and yield mostly ∼64 Ma ages. No older ages were obtained. More abundant gabbroic xenoliths are interpreted to represent mafic magmas emplaced into the middle to lower crust during this same approximate time span. The oldest surface rocks on Saint Lawrence Island include Paleozoic-Mesozoic shelfal units of the Brooks Range (once deposited on Precambrian basement) but xenolith age data suggest that such older rocks, if ever volumetrically important in the deeper crust, could have been reconstituted and remobilized during younger thermal and/or magmatic events. Conversely, Late Cretaceous to Paleocene magmatic rocks are likely increasingly important with depth in the crust. A similarly young age is inferred for the development of seismically imaged reflective crust and (by inference) the Moho beneath the Bering Shelf.